1982
DOI: 10.1038/ki.1982.130
|View full text |Cite
|
Sign up to set email alerts
|

Effect of alternate-day prednisone on plasma lipids in renal transplant recipients

Abstract: While numerous groups have reported high prevalences of plasma lipid abnormalities in their renal transplant recipients, we have been unable to confirm this finding. We have suggested that the routine use of alternate-day steroids (ADS) in our patients may be responsible. To test that hypothesis, a prospective controlled trial of equal total dose ADS versus daily steroids (DS) was conducted. Four months after transplant and before entering the trial, transplant study patients had significantly higher serum cho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1

Year Published

1987
1987
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(16 citation statements)
references
References 27 publications
1
14
1
Order By: Relevance
“…Vathsala et al [4]observed a 38% incidence of hypercholesterolemia, which occurred within 6 months following transplantation in 82% of patients. The serum HDL cholesterol content has been reported to be low by some authors [35, 38], but has also been found by others to be normal or elevated [39, 40, 41]. PON is a HDL-associated enzyme that can inhibit LDL oxidation [42, 43].…”
Section: Discussionmentioning
confidence: 99%
“…Vathsala et al [4]observed a 38% incidence of hypercholesterolemia, which occurred within 6 months following transplantation in 82% of patients. The serum HDL cholesterol content has been reported to be low by some authors [35, 38], but has also been found by others to be normal or elevated [39, 40, 41]. PON is a HDL-associated enzyme that can inhibit LDL oxidation [42, 43].…”
Section: Discussionmentioning
confidence: 99%
“…23 Changes in the lipid profile can include increased VLDL, total cholesterol, and triglyceride levels and decreased HDL-C levels. [24][25][26] Cyclosporine is thought to inhibit bile acid synthesis, bind to and block the LDL receptor, and reduce activity of lipoprotein lipase while increasing activity of hepatic lipase, all of which can promote increases in LDL-C. 26,27 Nontransplantation subjects receiving cyclosporine for other indications exhibit increased LDL-C. 27 It has been shown to raise total cholesterol and LDL-C in recent study of renal transplantation patients with stable renal function 28 and to increase lipoprotein (a) levels in renal transplantation recipients. 27 Cyclosporine can also inhibit prednisone metabolism and exacerbate the glucocorticoid effects in patients treated with both agents.…”
Section: Causes Of Dyslipidemia In Transplantation Patientsmentioning
confidence: 99%
“…The prevalence of dyslipoproteinemia varies, ranging from 16 to 72% of patients [3][4][5][6][7][8][9], These abnormalities include elevated total plasma triglyceride (TG) and cholesterol (C) as well as elevations of very low density lipoprotein (VLDL) and low-density lipoprotein (LDL) cholesterol. High-density lipoprotein (HDL) cholesterol levels have been reported to be low in some studies [9,10] but normal or elevated in others [11,12]. Information on the distribu tion of cholesterol in HDL subfractions is not available.…”
Section: Introductionmentioning
confidence: 99%